Business and Society: Determinants and Experiences of Corporate Social Responsibility Practices in Zimbabwean Extractive Industries from 2000-2015 - Mathende, Takudzwa Leonard; Nhapi, Tatenda Goodman (Consilience, 2017)
Although a considerable Corporate Social Responsibility (CSR) knowledge base exists in Zimbabwe, there have been no comprehensive studies on CSR determinants and community CSR in Zimbabwe since 2000. This article explores the dominant narratives in CSR literature that have contributed to continuous debates in related academia, businesses, and society. Zimbabwe is resource rich, but the majority of the population is still living in abject poverty. Some have questioned whether this is indicative of a Zimbabwean resource curse. Many Zimbabweans believe that the companies benefitting from these resources should finance social programs in the country (NewsDay, 2012). This belief is a result of fiscal challenges that the government of Zimbabwe is grappling with. The article concludes by recommending pathways for sustainable CSR implantation.